Chili-supplemented food decreases glutathione-S-transferase activity in Drosophila melanogaster females without a change in other parameters of antioxidant system. (31st December 2022) - Semaniuk, Uliana V.; Gospodaryov, Dmytro V.; Strilbytska, Olha M.; Kucharska, Alicja Z.; Sokół-Łętowska, Anna; Burdyliuk, Nadia I.; Storey, Kenneth B.; Bayliak, Maria M.; Lushchak, Oleh
ABSTRACT: Objectives: Many plant-derived anti-aging preparations influence antioxidant defense system. Consumption of food supplemented with chili pepper powder was found to extend lifespan in the fruit fly, Drosophila melanogaster . The present study aimed to test a connection between life-extending effect of chili powder and antioxidant defense system of D. melanogaster . Methods: Flies were reared for 15 days in the mortality cages on food with 0% (control), 0.04%, 0.12%, 0.4%, or 3% chili powder. Antioxidant and related enzymes, as well as oxidative stress indices were measured. Results: Female flies that consumed chili-supplemented food had a 40–60% lower glutathione- S -transferase (GST) activity as compared with the control cohort. Activity of superoxide dismutase (SOD) was about 37% higher in males that consumed food with 3% chili powder in comparison with the control cohort. Many of the parameters studied were sex-dependent. Conclusions: Consumption of chili-supplemented food extends lifespan in fruit fly cohorts in a concentration- and gender-dependent manner. However, this extension is not mediated by a strengthening of antioxidant defenses. Consumption of chili-supplemented food does not change the specific relationship between antioxidant and related enzymes in D. melanogaster, and does not change the linkage of the activities of these enzymes to fly gender.